2014
DOI: 10.3892/ol.2014.2302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the ‘not otherwise specified’ subtype in candidates for resectable non-small cell lung cancer

Abstract: The histological subtype of non-small-cell lung cancer (NSCLC) is a significant factor when selecting treatment strategies. However, cases are occasionally encountered that are diagnosed as ‘not otherwise specified’ (NOS) prior to surgery, due to an uncertain histological subtype. The present study investigated the prognostic significance of the NOS subtype for patients with resectable NSCLC. Between 2001 and 2011, 1,913 patients were diagnosed with NSCLC using transbronchial biopsy and underwent surgical rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Pursuit of tissue for mutation testing is encouraged in older patients and those presenting with poor PS, particularly where linked to lung cancer burden, with adverse survival outcomes for patients not tested vs negative for mutation attributed to these factors in multivariate analyses. Conversely, patient factors did not explain the adverse prognosis of patients with NSCLC NOS in our study, a finding supported by other studies ( Righi et al , 2014 ; Tane et al , 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…Pursuit of tissue for mutation testing is encouraged in older patients and those presenting with poor PS, particularly where linked to lung cancer burden, with adverse survival outcomes for patients not tested vs negative for mutation attributed to these factors in multivariate analyses. Conversely, patient factors did not explain the adverse prognosis of patients with NSCLC NOS in our study, a finding supported by other studies ( Righi et al , 2014 ; Tane et al , 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…The NSCLC, NOS group showed the highest metastasis rate (52.1%), which was higher even than that of the SCLC group (51.7%). This result is consistent with those of several previous studies, which suggested that the diagnosis of NSCLC, NOS is a poor prognostic factor on its own [ 19 , 20 ]. However, this should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 94%
“…[28] Moreover, the NOS subtype of NSCLC represented 12.6% of reported pathology in our study, which was relatively high in comparison to SEERS data, in which NOS represented 2.9% of NSCLC subtypes. [29] It is crucial to identify the subtype of NSCLC histopathology as it predicts the prognosis and directs the type of therapy for each subtype. For example, anti-EGFR tyrosine kinase Inhibitors and anti-ALK therapy are working with AC, and anti-angiogenesis therapy is associated with bleeding in squamous pathology.…”
Section: Discussionmentioning
confidence: 99%